2016
DOI: 10.1177/0194599816638084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Robotic versus Conventional Selective Neck Dissection and Total Thyroidectomy for Papillary Thyroid Carcinoma

Abstract: Compared with conventional transcervical SND with total thyroidectomy, robotic SND with total thyroidectomy yields superior outcomes for cosmetic satisfaction, longer operative time, and higher chest pain in the short term. Further study with a larger number of patients is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 31 publications
(138 reference statements)
2
41
0
Order By: Relevance
“…In our literature review, we found that our experience of needle‐assisted endoscopic LND technique was associated with higher lymph node yield compared with any other studies listed in Table . As seen in Figure , we completely removed the lymph nodes and relative soft tissues at level II and around the venous angle without remaining visible structural disease, intraoperatively.…”
Section: Discussionmentioning
confidence: 79%
“…In our literature review, we found that our experience of needle‐assisted endoscopic LND technique was associated with higher lymph node yield compared with any other studies listed in Table . As seen in Figure , we completely removed the lymph nodes and relative soft tissues at level II and around the venous angle without remaining visible structural disease, intraoperatively.…”
Section: Discussionmentioning
confidence: 79%
“…None of the studies had randomization performed between the two groups. Six of the studies involved patients with head and neck malignancy who underwent a retroauricular approach to the neck, whereas five of the studies consisted of patients with PTC who underwent a transaxillary approach. The total sample sizes ranged from nine to 143, whereas the robotic and conventional group sample sizes spanned from three to 62 and six to 102, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Following this, Kim et al combined the facelift and transaxillary approach to perform neck dissections in head and neck squamous cell carcinoma. Multiple case series and comparative studies, primarily out of South Korea, subsequently highlighted the feasibility of nodal dissection through robotic transaxillary, retroauricular, and modified facelift approaches . Despite the embrace of this technology in East Asia, studies remain limited in the head and neck surgical literature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that patients who undergo endoscopic or robotic surgery on the neck or thyroid suffer from moderate to severe neck, anterior chest, and axillary pain following surgery. [1,3] In addition, about 70% of patients complain of anterior chest discomfort within 4 days after endoscopic thyroidectomy, [4] and hypoesthesia with discomfort to the anterior chest area may persist for 3 months following surgery. [5] Postoperative pain is associated with reduced quality of recovery, delayed mobilization, prolonged hospitalization, and the development of chronic pain syndrome.…”
Section: Introductionmentioning
confidence: 99%